The visitors’ satisfaction visiting Kuala Lumpur and Selangor recreational parks - Azenan, Muhamad Farhan; Ab Rahman, Syakir Amir; Mahamod, Lukman Hakim (UiTM Press, 2021)
A rapid urbanization throughout the years leads to environmental issues and give damage to natural settings. The city needs a recreational park to live the society for many physical and social activities. The study aims to identify the factors influencing visitors’ satisfaction to recreational park in four selected parks in Kuala Lumpur and Selangor, namely Taman Tasik Shah Alam, Taman Tasik Titiwangsa, Taman Metropolitan Kepong, and KLCC Park. A total of 100 respondents were involved with a convenience sampling method. Three key attributes were asked in the survey including degree of comfort, accessibility and linkages, and facilities and amenities provided. The variable between the length of time spent in a visit and the satisfaction level of visitors towards recreational park were analysed. The research showed most of the respondents would spend for a moderate time followed by a long time when they satisfied with the attributes at recreational parks. The existing features provided shows an optimum level of performance and should be prepared of upcoming development. The study is significant to improve the facilities and programs of recreational parks in Malaysia hence maximize the satisfaction of the visitors.